Pengaruh Displin Kerja dan Motivasi Terhadap Kinerja Pegawai pada Suku Dinas Kependudukan dan Pencatatan Sipil Kota Jakarta Pusat - Guntoro Muhammad Widito; Anjar Dwi Astono (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Public services are services that are the responsibility of the government to its citizens. This responsibility has been mandated in the 1945 Constitution. The purpose of providing public services is the fulfillment of the basic rights needs of every citizen and resident of a product, service and or administrative service provided by the government related to the public interst. In the era of decentralization and the current stronger democrazition, the demands for public service responsibilities are also getting stronger and more prominent. Therefore, work discipline and motivation are very important employees to be able to produce good work performance and serve the community with passion and heart sincerely so that the community can be helped quiqkly and also get a positive image from the community itself.